PENGARUH HYPERTENTION SELF MANAGEMENT EDUCATION ( HSME) TERHADAP TEKANAN DARAH DI PUSKESMAS KABANJAHE - Lam Murni Sagala (Indonesian Trust Health Journal, 2019)
Hypertension is a persistent blood pressure with systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. The treatment of hypertension is highly depend on the information given by nurse to patients’ skills on self care management to modify and maintain effective behavior. These activities include self management in prescribed medication, health monitoring, adequate rest, stress management and prescribed diet and exercises. The purpose of this study was to determine the effect of Hypertension Self Management Education (HSME) on controlling blood pressure in hypertensive patients in the Kabanjahe health center.This research used the quasi experimental research, using pretest and posttest with control group design. The samples of research consisted of 40 respondents, and they were divided into two groups, namely: control group and intervention group. The data of research were analyzed by using the Paired T-test. The result of research shows that the p-values of Paired T-test of the experiment and control groups were 0.782 and 0.577 respectively whereas the p- value of Independent T-test was 0.001 (p <α; α = 0.05). Thus, there was an effect of Hypertention Self Management Education (HSME) on the control of blood pleasure of the patient hypertention, Community Health Center, Kabanjahe. The nurses, therefore, are suggested to extend the HSME to control the blood pleasure hypertention client and and utilize the HSME as a health promotion program. Hipertensi adalah tekanan darah persisten dengan tekanan darah sistolik di atas 140 mmHg dan tekanan darah diastolik di atas 90 mmHg. Perawatan hipertensi sangat tergantung pada informasi yang diberikan oleh perawat kepada keterampilan pasien tentang manajemen perawatan diri untuk memodifikasi dan mempertahankan perilaku yang efektif. Kegiatan-kegiatan ini termasuk manajemen diri dalam pengobatan yang diresepkan, pemantauan kesehatan, istirahat yang cukup, manajemen stres dan diet dan olahraga yang ditentukan. Tujuan penelitian ini untuk mengetahui pengaruh Hypertention Self Management Education (HSME) terhadap pengontrolan tekanan darah pasien hipertensi di puskesmas kabanjahe. Metode penelitian adalah quasi experimental dengan menggunakan metode pre-test and post-test with control group design. Sampel penelitian terdiri dari 40 responden, dan mereka dibagi menjadi dua kelompok, yaitu: kelompok kontrol dan kelompok intervensi. Data penelitian dianalisis dengan menggunakan Paired T-test. Hasil penelitian menunjukkan bahwa nilai-p dari uji-T Berpasangan dari eksperimen dan kelompok kontrol masing-masing adalah 0,782 dan 0,577 sedangkan p-nilai dari Independent T-test adalah 0,001 (p <α; α = 0,05). Dengan demikian, ada efek dari Edukasi Manajemen Diri Hipertensi (HSME) pada kontrol tekanan darah dari pasien hipertensi, Puskesmas, Kabanjahe. Oleh karena itu, perawat disarankan untuk memberikan penkes HSME untuk mengendalikan tekanan darah pasien hipertensi dan memanfaatkan HSME sebagai program promosi kesehatan.